Anti-Helicobacter pylori antibody status is associated with cancer mortality: A longitudinal analysis from the Japanese DAIKO prospective cohort study. - Satoshi S Nishizuka; Masahiro Nakatochi; Yuka Koizumi; Asahi Hishida; Rieko Okada; Sayo Kawai; Yoichi Sutoh; Keisuke Koeda; Atsushi Shimizu; Mariko Naito; Kenji Wakai (Public Library of Science (PLoS), 2023)
Paradoxically, patients with advanced stomach cancer who are Helicobacter pylori-positive (HP+) have a higher survival rate than those who are HP-. This finding suggests that HP infection has beneficial effects for cancer treatment. The present study examines whether HP+ individuals have a lower likelihood of death from cancer than those who are HP-. Prospective cohort data (n = 4,982 subjects enrolled in the DAIKO study between 2008-2010) were used to assess whether anti-HP antibody status was associated with cancer incidence. The median age in the primary registry was 53 years-old (range 35-69 years-old). Over the 8-year observation period there were 234 (4.7%) cancer cases in the cohort and 88 (1.8%) all-cause deaths. Urine anti-HP antibody data was available for all but one participant (n = 4,981; 99.98%). The number of HP+ and HP- individuals was 1,825 (37%) and 3,156 (63%), respectively. Anti-HP antibody distribution per birth year revealed that earlier birth year was associated with higher HP+ rates. With a birth year-matched cohort (n = 3,376), all-cancer incidence was significantly higher in HP+ individuals than those who were HP- (p = 0.00328), whereas there was no significant difference in the cancer death rate between HP+ and HP- individuals (p = 0.888). Cox regression analysis for prognostic factors revealed that the hazards ratio of HP+ was 1.59-fold (95%CI 1.17-2.26) higher than HP- in all-cancer incidence. Potential systemic effects of HP+ status may contribute to reduced likelihood of death for patients after an initial diagnosis of cancer.